FORMULASI DAN UJI STABILITAS FISIK GEL ANTIJERAWAT EKSTRAK ETANOL DAUN SURUHAN (Peperomia pellucida L.) - Arfiani Arifin; Intan Intan; Nur Ida (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Suruhan leaves (Peperomia pellucida L.) are known to be rich in secondary metabolites including alkaloids, flavonoids, saponins, tannins and triterpenoid compounds that have potential as anti-acne so that they can be applied as active ingredients in gel preparations. The purpose of this study was to determine the best base for the formulation of an anti-acne gel preparation of suruhan leaf extract that was physically stable. The research method includes the extraction of suruhan leaves by maceration using 96% ethanol. The gel formulation was designed with variations of carbopol base, HPMC, and Na CMC with a concentration of 2%. Physical stability tests include organoleptic, homogeneity, pH, dispersion, viscosity and adhesion which were carried out before and after accelerated storage using a climatic chamber. The results of this study showed that the gel preparation of the ethanol extract of suruhan leaves using carbopol and HPMC bases produced a physically stable gel based on the results of organoleptic tests, homogeneity, pH, dispersibility, adhesion and viscosity, before and after accelerated storage.